Pendampingan Pemantauan Laju Abrasi Pantai AURI Kota Balikpapan - Rian Sumendar; Bintang Ekananda; Nurbia (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The purpose of community service activities is to assist in monitoring beach abrasion as a form of concern for the environment and management of regional potential owned by the people of Sepinggan District, Balikpapan. In carrying out this activity several problems were found, including the coastline having reached land about 10-12 meters and reduced vegetation cover around the coast. Based on the results of this monitoring assistance, it was concluded that the handling of AURI Balikpapan City beach abrasion needs to be followed up with several action plans including installing breakwater on the affected shoreline, rebuilding damaged retaining walls, and increasing vegetation cover in the coastal area of ​​AURI City Balikpapan.